Reduced default mode network functional connectivity correlates with stroke and uncontrolled hypertension among patients with Alzheimer’s disease: an fMRI study in Klang Valley Malaysia - Suppiah, Subapriya; Ibrahim, Buhari; Seriramulu, Vengkatha Priya; Mohamad, Mazlyfarina; Piersson, Albert Dayon; Razali, Rizah Mazzuin; Hassan, Hasyma Abu; Ibrahim, Normala; Abdullah, Syahrilnizam; Ibrahim, Nur Shahidatul Nabila; Azmi, Nur Hafizah Mohad (Universiti Sultan Zainal Abidin, 2025)
Background: Risk factors for cardiovascular disease (CVD) have been increasingly implicated in the development of dementia as Alzheimer’s disease (AD) and tagged as Type III diabetes. Nevertheless, there is limited data on these metabolic effects upon the brain morphological changes and neuronal functional connectivity (FC). Our study was undertaken to predict the neuroimaging biomarkers of brain structural and functional abnormality with regards to CVD risk factors in AD patients compared to age-matched cognitively healthy controls (HC) in central Malaysia. Methodology: A phase I cross-sectional study of patients presenting with memory impairment and cognitive decline was conducted in the memory clinic at Hospital Kuala Lumpur (HKL). Sociodemographic data, neuropsychological test scores, and CVD risk factors were reviewed from medical records data from 2014 to 2019 and analysed based on patients diagnosed with various neurocognitive disorders. The second phase of the study involved recruiting AD subjects from HKL, Hospital Pengajar UPM and Klinik Kesihatan Pandamaran, Selangor as well as HC subjects from Klang Valley for a functional MRI study. Differences in CVD risks factors, grey matter volume (GMV) deficit, and neuronal FC were compared between AD and HC. Results: In phase I study, a total of 298 patients (30 MCI, and 268 dementia) were evaluated, with dementia patients consisting of 78 Alzheimer’s disease (AD), 93 Vascular dementia (VaD), 94 Mixed dementia, 2 early-onset Alzheimer’s disease (EOAD) and 1 Logopenic Progressive Aphasia type of AD (LPA). History of stroke was strongly associated with MCI and dementia (p=0.023). Hypertension was associated with diagnosis of AD but did not achieve statistical significance (p = 0.168). AD patients had reduced GMV compared to HC in the right medial temporal lobe, left fusiform, right medial occipital region right superior temporal lobe and right parahippocampal region (p-value < 0.05). There was significantly reduced functional connectivity in the default mode network of AD compared to HC. Conclusion: Hypertension, history of stroke, imaging biomarkers of reduced GMV at medial temporal lobe and decreased functional connectivity at DMN are predictors of Alzheimer’s disease among the patients in a central Malaysian population. Thus, monitoring these parameters and lifestyle modifications are recommended to alleviate these risk factors to delay the onset of AD.